Effects of Straw at Different Fermentation Phases on Soil Nutrient Availability and Microbial Activity - Chen, Tian; Mei, Yuxia; Liu, Xinwei; Zhao, Zhuqing; Liang, Yunxiang (Agronomy (Basel), 2024)
Returning corn straw to the field is beneficial for improving soil fertility, but the fermentation phase significantly affects the dissolved organic carbon (DOC) content. However, there is limited research on the effects of straw at different fermentation phases on soil microorganisms and soil nutrients. This study examined the effects of high-temperature fermentation phase straw (HF) and completely fermentation phase straw (CF) on soil nutrient activation and microorganism activity through pot experiments. The pot experiment results indicated a significant increase in soil DOC content following the application of corn straw, among which the high-temperature fermentation phase straw treatment (THF) exhibited the highest DOC content, which was 14% higher than the completely fermentation phase straw treatment (TCF). THF also significantly increased soil alkaline hydrolyzed nitrogen and available phosphorus content as well as urease and phosphatase, and promoted the uptake of nitrogen and phosphorus from soil by Brassica chinensis. THF significantly enhanced bacterial diversity and reduced the presence of pathogenic fungi. Compared to the TCF, the relative proportion of Fusarium under the THF decreased by 32.24%, effectively mitigating the impact of pathogenic fungi. THF also increased soil DOC content, enriched beneficial microbial community structure, increased soil enzyme activity, activated soil nutrients, thereby promoting the uptake of nitrogen and phosphorus by crops. Taken together, the results reveal that the application of high-temperature fermentation phase straw is conducive to soil fertilization and crop growth.